PENGARUH PRODUK WISATA DAN CITRA DESTINASI TERHADAP KEPUTUSAN UNTUK BERKUNJUNG KE PANTAI LON MALANG - Ardianto, Ferry Roy; Chrismardani, Yustina (JURSIMA, 2022)
Sampang Regency in East Java, Indonesia, has great potential in tourism. With its strategic location between Bangkalan and Pamekasan, and flanked by the Java Sea, Flores Sea, and Madura Strait, Sampang Regency offers natural beauty, rich culture, unique culinary, and friendly people. One of the interesting destinations that attracts attention is the Lon Malang Beach Tourism Village on Madura Island, Sampang Regency. Factors such as strategic location, ease of access, unique concept, safe environment, and adequate facilities are key factors in attracting visitors. A strong and positive destination image can influence tourists' interest in visiting a place, while attractive tourism products and good services also play a key role. This research uses a quantitative approach with data collection through questionnaires distributed online to 86 respondents who have knowledge or experience related to Lon Malang Beach in the past year. The results of this study are expected to provide deep insight into the factors that influence tourists' decision to visit Lon Beach Malang.